Vihodtsevski’s collection of the flora of Mt. Vitosha Bulgaria in SOM Herbarium at the Bulgarian Academy of Sciences - Lambevska-Hristova , Aneta; Bancheva, Svetlana (Biologia Serbica, 2019)
The Herbarium (SOM) of the Department of the Institute of Biodiversity and Ecosystem Research at the Bulgarian Academy of Sciences, is one of the largest Herbaria in the Balkans. Of particular interest are the specialized collections stored in the herbarium; including the thematic collection of researcher Nikolay Vihodtsevski, which represents the plant diversity of Mt. Vitosha, near Sofia, Bulgaria. Even today, this collection is of great importance for the study of plant diversity in Bulgaria.